New Paradigms and Future Critical Directions in Heterogeneous Catalysis and Multifunctional Reactors. Issue 1 (2nd January 2017) - Gogate, Makarand R.
Abstract : Heterogeneous catalysis is a key pillar of the global industrial chemical and petrochemical sector, and 85% of all chemical products are produced with at least one catalytic step. Indeed, catalysis and catalytic reactors are a critical underpinning science for energy, environmental, and economic security. This paper reviews some future critical directions for research in catalysis science, toward a greener and more sustainable future. We believe that even a relatively mature field as heterogeneous catalysis and nanomaterials can be vitalized and spurred by major discoveries, but an outside-the-box thinking and a focused effort in a large plurality of disciplines is necessary. Thus, critical research needs in several areas, including heterogeneous and homogeneous catalysis, biocatalysis, photocatalysis, electrochemical conversions, and computational catalysis, are reviewed. The research needs of the future lie at the intersection of synthesis of novel nanostructured materials with tunable pore size distribution, controlled porosity, and high surface area; development of new catalytic applications for such materials; and the science of advanced characterization including in situ spatiotemporal analysis. In the area of computational catalysis, we believe that the future lies in the development of hybrid methods (parallel and serial) which can model the typical multiscale phenomena that are typically encountered in protein translocation and signal transduction, charge transport, enzymatic catalysis, surface chemistry, and self-assembly in complex fluids. As we promulgate the new directions to the catalysis fraternity, some prior research areas will unfortunately need to be relegated to obsolescence, to maintain a healthy balance on the research forefront.